Enhancing Arabic Reading with the Scramble Technique: A Classroom Trial and Conceptual Framework at Al-Falah Islamic Junior High School - Siti Meila Asmawati; Ahmad Faroji (Lingu, 2025)
Purpose – This study examined whether the scramble technique improves Arabic reading skills among seventh-grade learners at Al-Falah Islamic Junior High School (Cikeusik, Pandeglang) and, in parallel, developed a coherent conceptual framework to guide its classroom use. Design/methods/approach – The research combined a conceptual framework development approach—synthesizing insights from educational psychology, second-language acquisition, and Islamic pedagogy—with a small quasi-experimental classroom trial. Two intact classes were assigned as experimental (scramble) and control (regular instruction); Arabic reading comprehension was measured using pre-/post-tests vetted through expert review and item validity checks, while normality diagnostics justified parametric inference. Findings – Descriptively, the experimental mean rose from 57.83 (pretest) to 88.57 (posttest; range 85–95); an independent-samples test contrasting the experimental mean (88.57) with the control mean (51.82) yielded t = 2.107 with a standard error of 17.44, indicating a statistically testable difference consistent with meaningful classroom gains. Mechanistically, the framework posits that scramble tasks consolidate form–meaning mappings, support morphological and interclausal processing, and foster collaborative engagement, thereby linking cognitive and motivational pathways to improved comprehension. Research implications – The study contributes context-specific evidence for beginner-level Arabic, offers a portable implementation cycle (orientation–reconstruction–verification–reflection), and articulates principles to align assessment with literal, inferential, and evaluative indicators. Limitations include intact-class assignment, a modest sample, and short-term measurement, which temper generalizability. Future work should employ cluster randomization or crossover designs, incorporate process-tracing (e.g., think-alouds), monitor fidelity and effect sizes, and test combinations with explicit metacognitive strategy instruction and subgroup analyses by baseline vocabulary